T-cell lymphoma in the tongue of a dog with cutaneous and striated forelimb muscle involvement - Raposo-Ferreira, Talita Mariana Morata [UNESP]; Jark, Paulo Cesar [UNESP]; Varallo, Giovanna Rossi [UNESP]; Borin-Crivellenti, Sofia [UNESP]; Tinucci-Costa, Mirela [UNESP]; Laufer-Amorim, Renée [UNESP]; De Nardi, Andrigo Barboza [UNESP] (My University, 2014)
Background: Primary tongue tumors rarely affect dogs and correspond to 4% of tumors involving the oropharynx. Until now, primary tongue lymphoma had not been reported. However, lymphoma involvement in the skeletal muscle, although quite unusual, was described in the literature in four cases. Cutaneous lymphoma is another rare extranodal manifestation. The objective of this report is to describe a case of T immunophenotype lymphoma occurrence, whose manifestation is atypical, not only because it is situated in the tongue muscle but also because of the subsequent involvement of the striated musculature of the left forelimb and the skin, which showed unfavorable evolution. Case: A female seven-year-old mongrel was seen showing a regular lump in the base of the tongue, 3 cm in diameter, not ulcerated and of firm consistency, with halitosis as the only clinical sign of the disease. Incisional biopsy of the lump was performed and histopathology verified that it was large cell lymphoma. The material was sent for immunohistochemical evaluation and was characterized as T immunophenotype lymphoma by positive CD3 and negative CD79a marking. The CHOP (cyclophosphamide, doxorubicin, vincristine and prednisone) chemotherapy protocol was established as treatment and after the first chemotherapy session there was partial remission of the mass, measuring 2 cm in diameter. The lump, however, remained stable in the following sessions. Thirty days after the diagnosis of lymphoma, the animal began to show lameness of the left forelimb and swelling near the head of the left humerus. A muscle mass, firm in consistency, progressing fast, presented a significant increase, just three weeks after its appearance. Two skin lesions, arcuate, erythematous and pruritic also appeared in the dorsocervical and ventral-abdominal region. Incisional biopsy of these lesions was performed and the histopathological diagnosis confirmed muscle and cutaneous large cell lymphoma and immunophenotype compatible with T cells (positive CD3 and negative CD79a). Due to disease advance, even during chemotherapy, a rescue protocol of L-asparaginase administration followed by lomustine and prednisone was proposed. Even with the rescue protocol there was no remission of the tumors and the case was classified as progressive. The animal of this report died after completing the first cycle of chemotherapy protocol, with a survival of 92 days. Discussion: Despite the fact that clinical behavior of primary lymphoma in dogs' skeletal muscle is unknown, it is believed that, as in humans, it can be associated with chronic inflammation or neoplastic cell invasion by proximity of the tumor or metastasis, which could justify the dissemination of the lymphoma reported here from the tongue to other tissues. However, appearance of concurrent independent lymphomas cannot be ruled out. As observed in the three cases of primary muscular lymphoma, the dog of this report had low response to therapy and short survival. This report presents the first case of lymphoma in tongue with subsequent skin and left forelimb skeletal muscle involvement described in the literature. The clinical outcome corroborates the aggressiveness of muscular lymphoma observed in the other reports and also suggests that both tongue and other skeletal muscle tumors should be included in the differential diagnosis of canine lymphoma.
Keywords: Dog; Lymphoma; Skeletal muscle; Tongue